Big Data Analytics and Investment Decision-Making: The Mediating Effect of Quality Characteristics of Accounting Information - Insights from Accounting Professionals - Krishnasamy Tharsika; Senthuran, Varanitha; Ganeshamoorthy, Thaneshan (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2025)
This study investigates the mediating role of accounting information quality in the relationship between big data analytics and investment decision-making. Using data from 100 accounting professionals in Sri Lanka, the study employs PLS-SEM to analyze the influence of big data attributes—volume, variety, and velocity—on accounting information quality and investment decisions. The results reveal that big data analytics significantly improves accounting information quality, which in turn strongly influences investment decisions. However, there is no direct impact of big data on investment outcomes, confirming a full mediation effect. These findings underscore the importance of enhancing data quality alongside technological adoption to drive strategic financial decisions. Implications for theory and practice are discussed, with suggestions for future research in cross-national and contextual settings.